O Museu do Ipiranga e a instrução pública no estado de São Paulo: um estudo sobre o atendimento ao público (1895 a 1915) - Stepanenko, Igor (2016)
This text aims to understand how public service was held in the Museu Paulista do Ipiranga Museum, or, as it is known, in the period of 1895, date of its Foundation, until 1915, when its first Director Herman Von Ihering leaves his post, and the Museum was founded as the Museum of Natural history, begins slowly becoming Historical Museum under the direction of Alfonso Taunay. Seeks to map the intellectual debate that turned into a monument to independence, but reasoned as scientific character Museum. The hypothesis of this study is that, for a portion of the Republicans from São Paulo, Museu Paulista functioned as educational institution within a general project of public instruction, in addition to scientific and production site, too, as supplementary instruction to schools. . For both the research bolsters file documents, lectures, letters, letters, newspapers, magazines, specialized bibliography